Game creativity as a method of socialization and space of the sociocultural interaction of adults and teenagers - Казарова, Ганна Миколаївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
In the article the problem of socialization of teenagers has been analyzed as the most important and at the same time the most difficult stage in development of the personality.Game methods of socialization of the teenagers that appeared to be effective at various stages of historical development, as the possibility of implementation of sociocultural interaction between adults and teenagers have been considered. It is emphasized that teenage role play is a psychological feature of this age and one of the most important methods of socialization and self-determination in culture.Game creativity of teenagers appears in its existence and implementation so closely connected with sociocultural realities of anysociety that becomes a factor which actively influences on big changes of these realities